In Vitro Anti-Mycotoxigenic and Anti-Aflatoxigenic Properties of Probiotic Bacteria; Lactobacillus plantarum and L. paracasei - Abdolamir Allameh; F. Ani; M. Shams-Ghahfarokhi; M. Razzaghi-Abyaneh (Journal of Sciences, Islamic Republic of Iran)
The present study was designed to examine the effects of Lactobacillus plantaraum and L. paracasei on the growth and aflatoxin-producing ability of Aspergillus parasiticus. In these experiments, direct and indirect interactions of two different probiotic lactobacilli with A. parasiticus was examined.A co-culture system which supported both fungal growth and probiotic bacteria showed the inhibitory actions of the lactobacilli on A. parasiticus growth. Disk Diffusion Assay was developed to examine the anti-fungal action of the probiotic cell free extract.  The probiotic extracts were also applied in a micro-dilution assay to evaluate the anti-fungal and anti-aflatoxin properties of the probiotic extracts. The results showed that direct interaction of the bacteria with A. parasiticus in a spot-culture method (two-layer semi-solid/solid culture) caused a clear zone of inhibition of A. parasiticus growth. Fungal growth inhibition was found to be dependent on the concentration of the probiotic extracts added to A. parasiticus culture (micro dilution assay). The inhibitory effects of the probiotic extracts was further confirmed using Disc Diffusion Assay by showing that discs loaded with 50 or 100 µl of extracts resulted in a significant (4-5 folds) inhibition in A. parasiticus growth. The extract prepared from the probiotics inhibited the fungal growth and at higher levels. Accordingly, the probiotic extract (50% v/v) could significantly suppress aflatoxin levels in mycelia and fungal culture media.  In conclusion, probiotic bacteria and their cell-free extracts produced under optimized condition exhibit anti-fungal and anti-mycotoxin effects provided that these bacteria undergo screening and selection prior totheir application.